Effects of self-management, education and specific exercises, delivered by health professionals, in patients with osteoarthritis of the knee - Coleman, S.; Briffa, Kathy; Carroll, G.; Inderjeeth, C.; Cook, N.; McQuade, J. (Biomed Central Ltd, 2008)
Background. An education self-management program for people with osteoarthritis (OA) of the knee was designed to be delivered by health professionals, incorporating their knowledge and expertise. Improvement in quality of life, health status and pain in response to this program has previously been demonstrated in an uncontrolled pilot study. To more rigorously test the effectiveness of the program we will undertake a randomised controlled trial of people with OA of the knee offering specific self-administered exercises and education, in accordance with the principles of self-management. Aim: To determine whether an education self management program for subjects with Osteoarthritis (OA) of the knee (OAK program) implemented by health professionals in a primary health care setting can achieve and maintain clinically meaningful improvements compared standard medical management in a control group. Methods. The effects of standard medical management will be compared with the effects of the OAK program in a single-blind randomized study. Participants: 146 male and female participants with established OA knee will be recruited. Volunteers with coexistent inflammatory joint disease or serious co-morbidities will be excluded. Interventions: Participants will be randomized into either intervention or control groups (delayed start). The intervention group will complete the OA knee program and both groups will be followed for 6 months. Measurements: Assessments will be at baseline, 8 weeks and 6 months. SF-36, WOMAC and VAS pain questionnaires will be completed. Isometric quadriceps and hamstring strength will be measured using a dynamometer; knee range of movement using a goniometer; and physical function will be determined by a modified timed up and go test. Data will be analysed using repeated measures ANOVA. Discussion. While there is evidence to support the effectiveness of SM programs for people with hypertension, diabetes and asthma, the evidence available for treatment of arthritis remains equivocal. The aim of this study is to determine the effectiveness of a disease specific self-management program for people with OA knee. The study design includes all the important features of a clinical experimental study to minimize bias so the results of the study will provide a high level of evidence. People with OA of the knee have identified pain and problems with daily activities as the most important problems associated with their condition. The outcome measures selected specifically address these issues and have demonstrated validity and are responsive within the range of change expected in response to the intervention. Hence the results of the study will reflect their priorities. The results of the study will provide evidence to guide clinicians and funding bodies seeking to establish priorities regarding the provision of this disease specific program. Trial registration. ACTR number: 12607000080426. © 2008 Coleman et al; licensee BioMed Central Ltd.